COMPREHENSIVE STEPS AND STRATEGIES TO EFFECTIVELY LEARN ENGLISH (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2024)
An increasingly interconnected world, the ability to speak English has become less of a desirable skill and more of a necessity. No longer confined to the halls of academia, English has taken its place as the dominant language of global communication, opening doors to a wealth of opportunities for those who master it. Here's why learning English is so crucial in the 21st century1: